A política da polícia militar do estado de São Paulo - Macedo, Henrique de Linica dos Santos (2022)
This thesis aimed understand how the ways of doing politics of the Military Police of the State of São Paulo produced the hegemony of ostensive policing. It was questioned how the corporation relates to other institutions in the criminal justice system; what is their orientation for designing their action policies; how they have shaped their structure and organization over the last thirty years; and how internal relationships interfere with police action. To this end, decrees that deal with the structure of the institution were analyzed, and interviews were conducted with military police officers of different hierarchies. The main results indicate that the Military Police of São Paulo: ostensive policing holds the monopoly of public security in the state, its managers gain more "power" within the institutional design of the executive and the legislative that value a militarized strategy in public security; the institution has expanded its territorial units, mainly to attend to the most diverse functions; there is a hierarchical imbalance, in which the most numerous enlisted personnel monopolize operational services, and officers see themselves as administrative managers; new information technologies have been incorporated to support operational planning and supervision of street service.